Recombinant Aspergillus fumigatus antigens Asp f 3 and Asp f 9 in liposomal vaccine protect mice against invasive pulmonary aspergillosis. Issue 31 (29th July 2022) - Slarve, Matthew; Holznecht, Nickolas; Reza, Hernan; Gilkes, Adrienne; Slarve, Ielyzaveta; Olson, Jon; Ernst, William; Ho, Sam On; Adler-Moore, Jill; Fujii, Gary
Highlights: Liposomal Vaccine protects mice against invasive aspergillosis. Protection is effective despite immunosuppression common to aspergillosis patients. Protection is robust to multiple azole-resistant fungal strains. This vaccine may have promise for clinical applications. Abstract: Invasive pulmonary aspergillosis caused by the ubiquitous mold Aspergillus fumigatus is a major threat to immunocompromised patients, causing unacceptably high mortality despite standard of care treatment, and costing an estimated $1.2 billion annually. Treatment for this disease has been complicated by the emergence of azole resistant strains of A. fumigatus, rendering first-line antifungal therapy ineffective . The difficulties in treating infected patients using currently available drugs make immunotherapeutic vaccination an attractive option. Here, we demonstrate the efficacy of VesiVax® adjuvant liposomes, consisting of a combination of two individual liposome preparations, to which two recombinant A. fumigatus surface antigens, Asp f 3 and Asp f 9 (VesiVax® Af3/9), have been chemically conjugated. Using a murine model, we demonstrate that VesiVax® Af3/9 is protective against infection by azole resistant strains of A. fumigatus in both steroid-suppressed and neutropenic mice as quantified by improved survival and reduced fungal burden in the lungs. This protection correlates with upregulation of IL-4 produced by splenocytes, and the presence of Asp f 3 and Asp f 9 specific IgG2a antibodies in the serum of mice given VesiVax® Af3/9. Furthermore, mice given VesiVax® Af3/9 with a subsequent course of liposomal amphotericin B (AmBisome®) had improved survival over those given either treatment alone, indicating a benefit to VesiVax® Af3/9 vaccination even in the case of infections that require follow-up antifungal treatment. These data demonstrate that prophylactic vaccination with VesiVax® Af3/9 is a promising method of protection against invasive pulmonary aspergillosis even as the changing face of the disease renders current therapies ineffective.